(untitled) (Teaching and Learning Inquiry, 2016)
This study evaluated a model of student-engaged educational development. Despite widespread commitment to student engagement across many institutional activities, student participation as partners with faculty in teaching and learning enhancement has been identified as a threshold concept for educational development. This study sought not only to establish a student-engaged model of teaching observation in a United Kingdom context, but also to critically examine the ways in which student, faculty, and developer participants conceptualise student expertise in relation to learning and teaching. Concept-map mediated interviews with students and faculty in humanities and healthcare subjects elicited conceptions and comparative knowledge structures of pedagogical intelligence for the purposes of enhancing teaching practice. The outcomes of the study are considered in relation to the theorisation of student engagement with particular focus on perspectives of expertise and power relations.